Depression, anxiety, coping skills, and quality of life among antenatal women - Mohd Arifin, Siti Roshaidai; Mohd Abadi, Nur Aqilah; Kamaruddin, Amalia; Mohd Mohadis, Hazwani; Abd Aziz, Karimah Hanim; Musa, Ramli; Muhammad, Noor Azimah; Abang Abdullah, Khadijah Hasanah; Syed Mohideen, Fathima Begum; Marhusin, Mohd Fadzli; Che Mat, Khairi; Mohd Noor, Hanisah; et al. (Universiti Putra Malaysia Press, 2025)
Introduction: Untreated antenatal depression and anxiety strongly reduce the quality of life and create a considerable economic and social burden on the individual, family, and community. Whilst there were few studies conducted on mental health among antenatal women in Malaysia, variables such as coping skills and quality of life were neglected in those studies. The aim of this study was to determine the prevalence of depression and anxiety among antenatal women in Kuantan, Pahang and its association with coping skills and quality of life. Methods: A quantitative cross-sectional study was conducted at seven antenatal clinics in Kuantan, Pahang. Participants were selected based on the inclusion and exclusion criteria. The questionnaire consisted of four parts: sociodemographic profiles, Edinburgh Postnatal Depression Scale (EPDS), Depression, Anxiety Stress Scale (DASS-21), Coping Skills questionnaire and Quality of Life and health literacy questionnaire. Data were analysed using descriptive statistics, Mann Whitney test and Spearman correlation. Result: A total of 224 antenatal women responded to the survey. The prevalence of depression and anxiety among antenatal women in Kuantan, Pahang was 29.9% (n=67) and 20.5% (n=46), respectively. The mean for coping skills and quality of life recorded was 39.75 (10.48) and 89.31 (16.60), respectively. The study also proved that there was an association between depression and anxiety with quality of life (p=0.000). A correlation was found between coping skills and quality of life (r=0.540, p=0.001). Conclusion: This study calls for a mental health screening during pregnancy, periodically counselling session and promoting mental health awareness can reduce depression and anxiety among antenatal women.